Implementasi Metode Problem-Based Learning berbantuan Video Tutorial pada Mata Pelajaran Dasar Ketenagalistrikan - Hamd, Walillaahil; Elfizon, Elfizon (Jurnal Pendidikan Teknik Elektro, 2025)
The low learning outcomes of students and the learning model applied to learning activities are less interesting for students to carry out learning activities, making students less able to understand the learning material presented. Therefore, it is necessary to take action to improve learning outcomes and student interest in learning activities. The purpose of this study was to determine the effectiveness of the Problem-Based Learning model assisted by video tutorials in improving learning outcomes in basic electricity subjects at SMKN 5 Solok Selatan. This study uses a quantitative research method using a quasi-experimental model with a one-group Pretest and Posttest design. The subjects in this study were students of class X TK B SMKN 5 Solok Selatan in the 2024/2025 academic year, with the number of students in class X TK B (15 students). Based on the results of the research that has been carried out, show that the Problem-Based Learning learning method significantly improves student learning outcomes. Based on the pretest data, many students have not achieved the KKTP score, with the majority of scores below standard. After implementing this method, the post-test results showed a significant increase with 80% of students successfully achieving or exceeding the completion standard. The effect size analysis shows that the impact of this method is large, indicating a substantial influence on improving student learning outcomes.